Anti‐IL17 and anti‐IL23 biologic drugs for scalp psoriasis: A single‐center retrospective comparative study. Issue 2 (30th November 2021) - Narcisi, Alessandra; Valenti, Mario; Cortese, Andrea; Toso, Francesco; Pavia, Giulia; Gargiulo, Luigi; Borroni, Riccardo; Costanzo, Antonio
Abstract: Scalp is a frequent localization of psoriasis that has a massive impact on patient's quality of life. Managing this psoriasis' manifestation is often challenging, thus biologic drugs are widely used as a treatment option in refractory scalp psoriasis. The aim of our study is to retrospectively compare the efficacy of anti‐interleukin (IL) 23 drugs (guselkumab, tildrakizumab, risankizumab) and anti‐IL17 or anti‐IL17RA biologics (secukinumab, ixekizumab, and brodalumab) in real‐life patients affected by scalp psoriasis. One hundred twenty‐seven patients with a clinical diagnosis of scalp psoriasis and a baseline scalp Physician Global Assessment ≥3 were enrolled; 65 patients were treated with anti‐IL23 and anti‐IL62 with anti‐IL17 or anti‐IL17RA. Statistical analysis trough χ 2 test was performed in order to evaluate the percentage of response among the two groups of patients. Responders' percentage of patients under anti‐IL23 was 41.5%, 75.4%, 88.1%, 87.5%, 93.7%, and 100% at Week 4, 16, 48, 96, and 144, respectively. In the group on anti‐IL17 was 62.9%, 90.3%, 91.2%, 97.3%, 96.9%, and 95.2% at Week 4, 16, 48, 96, and 144, respectively. Both anti‐IL17 and anti‐IL23 appeared to be effective on scalp psoriasis; in particular patients treated with anti‐IL17 drugs reached a faster significant reduction of the lesions; on the other hand, anti‐IL23 monoclonal antibodies were slightly superior in maintaining the clinical improvement through the follow‐up.